2005
DOI: 10.1016/j.adolescence.2005.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Video gaming promotes concussion knowledge acquisition in youth hockey players

Abstract: While the positive uses for video games in an educational setting have also been established, the educational aim is usually made explicit. The goal of this research was to develop a video game wherein the educational aspect was implicitly embedded in the video game, such that the gameing activity remained interesting and relevant. Following a pilot study to confirm the usability of an in‐house developed game, two studies were conducted with 11–17 year old hockey players (, ). Results demonstrated that partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…Because children and adolescents are the main target of educational games (Ratan and Ritterfeld 2009), a series of studies have investigated the effects of educational games on children (Goodman et al 2006;Klawe 1998). For example, Goodman and colleagues (2006) found that a game designed to teach adolescents about concussion symptoms significantly increased related knowledge among children between 11 and 17 years old.…”
Section: Advertising Literacy Educationmentioning
confidence: 99%
“…Because children and adolescents are the main target of educational games (Ratan and Ritterfeld 2009), a series of studies have investigated the effects of educational games on children (Goodman et al 2006;Klawe 1998). For example, Goodman and colleagues (2006) found that a game designed to teach adolescents about concussion symptoms significantly increased related knowledge among children between 11 and 17 years old.…”
Section: Advertising Literacy Educationmentioning
confidence: 99%
“…59 Educational methods are effective in increasing athletes' awareness of concussion symptoms. Goodman et al 60 found that exposure to a concussion-symptom video game improved symptom identification among youth ice hockey players. 60 Similarly, Bramley et al 61 noted that high school soccer players who received concussion education were more likely to report concussion symptoms to their coach.…”
Section: Documentation and Legal Aspectsmentioning
confidence: 99%
“…The results of this study indicate that further work is required on concussion education and compliance among hockey players, and that additional measures are required to improve compliance 22,23 . For example, would compliance with return to play advice be enhanced by requiring written approval by a physician of a player's readiness to return?…”
Section: Discussionmentioning
confidence: 99%